2017
DOI: 10.4317/jced.54261
|View full text |Cite
|
Sign up to set email alerts
|

Post-orthodontic position of lower incisors and gingival recession: A retrospective study

Abstract: BackgroundTo evaluate if changes in lower incisor position following orthodontic treatment are correlated with development of gingival recessions.Material and MethodsPre- and post-treatment digital models and lateral cephalograms of 22 subjects were collected retrospectively. The clinical crown length, gingival scallop, and papilla height of the central lower incisor were measured along with the cephalometric incisor’s inclination, the distance from the mandibular plane, and the distance between the Infradenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Despite these recommendations, there is a lack of scientific consensus and contradicting results that can be found in the literature [ 9 ]: Renkema and colleagues found that proclination of lower incisors did not increase the risk of gingival recession 5-year post-treatment in adolescents [ 10 ], and similarly, a systematic review concluded that no evidence can be found to confirm that proclination of lower incisors really affects the development of gingival recessions [ 11 ]. On the other hand, some studies on adolescent patients or mixed-age samples reported an increased risk of gingival recessions [ 12 , 13 ]. Vassalli et al [ 14 ] in their systematic review that included both animal and human studies concluded that a cause-effect relationship could be present but highlighted that this was supported by a low level of evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these recommendations, there is a lack of scientific consensus and contradicting results that can be found in the literature [ 9 ]: Renkema and colleagues found that proclination of lower incisors did not increase the risk of gingival recession 5-year post-treatment in adolescents [ 10 ], and similarly, a systematic review concluded that no evidence can be found to confirm that proclination of lower incisors really affects the development of gingival recessions [ 11 ]. On the other hand, some studies on adolescent patients or mixed-age samples reported an increased risk of gingival recessions [ 12 , 13 ]. Vassalli et al [ 14 ] in their systematic review that included both animal and human studies concluded that a cause-effect relationship could be present but highlighted that this was supported by a low level of evidence.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be kept in mind that the clinical relevance of the induced recession is unclear, and most studies have only documented the pre-or post-orthodontic incidence of gingival recession. 7,36,60,74,75 The strengths of this systematic review include the comprehensive search of the relevant literature, no restriction on the language or study design, and the quality assessment of the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 However, orthodontic appliances might increase plaque accumulation and impede proper oral hygiene, which raise the possibility of making these treatments detrimental to periodontal tissues. [5][6][7][8][9] Lindhe and Seibert 10 used the term "periodontal biotype" to describe morphologic characteristics of the periodontium. In general, there are two types of gingival biotype: "thin scalloped" and "thick flat."…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, various investigations have determined a higher prevalence for LGR after orthodontic Tx compared to untreated controls [6,7]. Particularly the proclination of lower incisors has been regarded as a risk factor [8][9][10]. Recent studies, on the other hand, could not confirm this presumption [11,12].…”
Section: Introductionmentioning
confidence: 99%